SOCIO-DEMOGRAPHIC DETERMINANTS OF CARDIOVASCULAR RISK FACTORS AMONG ADULTS IN SUBURBAN POPULATION OF SOUTH INDIA - SASIKALA PALAYAN; THENMOZHI PALUCHAMY; RAMESH CHANDRABABU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The shift in lifestyle among the South Asian population has significantly contributed to the increasing burden of non-communicable diseases. This study estimates risk factors of cardiovascular diseases (CVDs) among adults in South India. Methods: The current study used data from adults in sub-urban area of South India. The total sample for the analysis was 260 adults aged between 20 and 60 years. Prevalence of cardiovascular risk was assessed by the non-laboratory-based INTERHEART modifiable risk scale. The data on socio-demographic variables were expressed as a frequency table and analysed by the Chi-square test. The CVD risk was also analysed comparing age and gender by multiple logistic regression. Results: The mean age (standard deviation) of the adults was 35.38 (8.56) years. The frequency of risk factors for the age <39 years showed, 100,85.4, 64.4, and 26.7% for no risk, mild, moderate, and severe, while the above 40 years showed, 0, 14.6.35.6, and 73.3%. It was statistically significant (p<0.001), showing that the severity of the CVD risk is comparatively more in above 40 years. The age showed an odds ratio of 5.334, while the gender showed an odds ratio of 0.541. Conclusion: This screening study offers insights into the distribution of risk factors of CVDs among IT professionals, particularly concerning age and gender, poses a significant challenge to India`s future health trajectory. Implementing effective strategies focused on early detection and management is crucial to reducing the risk of CVDs.